Bismuth powder-bulk-modified carbon paste electrode for the voltammetric determination of Nitenpyram insecticide - Guzsvány, Valéria; Papp, Zsigmond; Švancara, Ivan; Vytřas, Karel (Univerzita Pardubice, 2011)
In this article, voltammetric investigation of a commercial neonicotinoid insecticide, Nitenpyram (Nit), was carried out using a bismuth powder-bulk-modified tricresyl phosphatebased carbon paste electrode (Bi-TCP-CPE). The effect of the content of bismuth and of the electrode pretreatment are evaluated. The surface structure of the working electrodes was tested using scanning electron microscopy coupled with energy dispersive spectrometry (SEM/EDS). Then, a new method employing the (direct) differential pulse voltammetry and the Bi5%-TCPCPE (i.e., with 5% Bi, w/w) has been proposed for the determination of Nit at the low g mL-1 concentration level.
Keywords: carbon paste electrode; tricresyl phosphate; bismuth powder; bulk modification; voltammetric determination; Nitenpyram